Keterampilan Dasar Mengajar Dalam Pembelajaranmatematika di SMP - Kristiana, Dini; Muhibbin, A. (Universitas Muhammadiyah Surakarta, 2018)
This study aims to describe (1) the skills of teachers in preliminary activities, (2) theskills of teachers in the core activities, and (3) the skills of teachers in closing activitiesin learning mathematics in class VIII students at SMP Negeri 2 Gatak Sukoharja. Thistype of research is a qualitative descriptive study with an ethnographic approach.Data collection techniques are interviews, observation, and documentation. Thevalidity of the research uses data source triangulation and triangulation techniquesor data collection methods. Data analysis in this study is interactive. Researchersobtained three findings, namely (1) Planning the basic teaching skills of teachersin mathematics learning beginning with the readiness of the teacher in preparinglearning tools, media, and teaching materials to be used, (2) Through clear vision,mission and goals the school makes programs that prioritize basic teaching skills forteachers and prospective teachers later, (3) Basic skills of teaching the whole teacherare good.